Produksi Biofuel Berbahan Baku Mangrove Untuk Substitusi Bahan Bakar Gasoline - Syarifudin, Syarifudin; Yohana, Eflita; , Muchammad; , Suhartana; Kusnadi; Fatkhurrozak, Faqih; Lukman Sanjaya, Firman (Infotekmesin, 2024)
Dependence on fossil fuels requires a solution through alternative fuels. Ethanol is the recommended solution because it is easy to produce using raw materials that are abundant in nature, such as mangrove fruit. The Rhizophora Mucronata type of mangrove fruit contains 45.22% carbohydrates and is not used as raw material for human food. The research aims to produce ethanol biofuel from mangrove raw materials using multistage distillation. Experimental methods were applied at the stages of mangrove flour production, mangrove flour property testing, saccharification and fermentation, mangrove ethanol distillation, and analysis of potential performance and exhaust emissions. The research produced mangrove biofuel with an alcohol content of 28% which was produced from mangrove flour and had an ash content of 1.91%, protein, 2.24%, fat 0.53%, and water 11.61%. In addition, mangrove biofuel has higher viscosity and density properties than Gasoline at 0.8067Cp and 0.8115 g per mL respectively. The use of mangrove biofuel as a result of experiments is predicted to reduce fuel injection performance.